Place attachment of railroad settlement residents, case study: Kampong Tenggumung, Surabaya City. Issue 1 (April 2021) - Ramadhani, A; Fatimah, E; Wartaman, A S
Abstract: Place attachment refers to the formation of one's inner bond with a place. Kampong Tenggumung is a housing area located on the edge of Sidotopo Railroad and currently most of its inhabitants are the third descendants of the original owner. It indicates the formation of place attachment of Kampong's residents toward their environment. Therefore, the research aims to identify the place attachment of Tenggumung's community towards their residential environment. The research method is descriptive qualitative. The study was done by understanding the process of settling and the concept of housing in Kampong Tenggumung through interviews and visual observations of residential areas, supported by map data on regional development. Then, the level of place attachment of the community to their residence was determined. The results showed Tenggumung's community who have formed a particular concept of dwelling, namely the orientation of West-East buildings, a house inhabited for up to 3 generations, the road as a space for interaction, the merging of private-public (semi-private) areas, and the linked activities of residents and the rail border. This showed the level of place attachment of the community towards their environment has reached Level 2 Personalized Attachment.